Effect Of Addition Of Ground Vegetable Oil Seeds On The Storage Stability Of Vacuum Packaged Spent Broiler Breeder Chicken Sausages - Indumathi, J; Shashikumar, M; Bhaskarreddy, G V; Babu, A Jagadeesh; Gnanaprakash, M (Journal of Meat Science, 2023)
Spent broiler breeder chicken sausages were developed by incorporated with 10% level of ground vegetable oilseeds (poppy, sesame and peanut) separately and were stored at refrigeration temperature (4±1°C) under vacuum packaging. The vacuum packaged low fat chicken sausages along with control were analyzed for physico- chemical, microbiological and sensory changes throughout the storage time at regular intervals. Results revealed that the vacuum packaged low fat chicken sausages had significantly (p < 0.05) lower FFA, TBARS, tyrosine values and microbial counts than control throughout storage period. Regardless of formulation, coli forms were not detected throughout the storage period in all vacuum packaged sausages. Among low fat treatments, sausages with ground sesame seed recorded significantly (P<0.05) lower microbial counts followed by ground peanut seed and ground poppy seed added sausages. Scores for all sensory attributes decreased significantly (P<0.05) during storage in refrigeration temperatures in all treatments irrespective of formulation. Regardless of formulation low fat chicken sausages along with control were spoiled after 30 days of refrigeration storage (4±1ᵒC). Combination of vacuum packing and fat replacement with ground vegetable oilseeds as natural antioxidants reduced lipid oxidation and microbial growth in sausages and maintained the sensory quality characteristics during refrigeration for 30 days.